Observed smoking in cars: a method and differences by socioeconomic area. Issue 5 (22nd September 2006) - Martin, Josh; George, Robert; Andrews, Kirsty; Barr, Peter; Bicknell, Derryn; Insull, Elizabeth; Knox, Carl; Liu, Jessie; Naqshband, Mumraiz; Romeril, Kate; Wong, Donny; Thomson, George; et al.
Abstract : Objectives: To establish a reproducible method to estimate he point prevalence of smoking and second-hand smoke (SHS) exposure in cars, and to compare this prevalence between two areas of contrasting socioeconomic status. Method: A method involving two teams of observers was developed and evaluated. It involved observing 16 055 cars in Wellington, New Zealand. Two of the observation sites represented a high and a low area of deprivation (based on a neighbourhood deprivation index) and three were in the central city. Results: A 4.1% point prevalence of smoking in cars was observed (95% confidence interval (CI) 3.8% to 4.4%). There was a higher prevalence of smoking in cars in the high deprivation area relative to the other sites, and particularly compared to the low deprivation area (rate ratio relative to the latter 3.2, 95% CI 2.6 to 4.0). Of cars with smoking, 23.7% had other occupants being exposed to SHS. Cars with smoking and other occupants were significantly more likely to have a window open (especially if the smoker was not the driver). The observation method developed was practical, and inter-observer agreement was high (κ value for the "smoking seen in car" category 0.95). Conclusions: Observational studies can be an effective way of investigating smoking in cars. The data from this survey suggest that smoking in cars occurs at a higher rate in relatively deprived populations and hence may contribute to health inequalities. Fortunately, there are a number of policy options for reducing SHS exposure in cars including mass media campaigns and laws for smoke-free cars.